Interview: Hans Horreus de Haas - Diederik Pomstra (EXARC, 2012)
December 2010, Hans de Haas turned 75 and this seemed a fitting occasion for an in depth interview with this Nestor of Dutch living prehistory and experimental archeology. In SPT Bulletin nr. 23 David Wescott and Steve Watts already published an interview with Hans, but there is more to say about this extraordinary man.